(untitled) (Research, Society and Development, 2021)
The transmissible venereal tumor is a neoplasm distributed worldwide that affects dogs mainly through sexual contact, the affected animals usually develop nodules in the lower reproductive tract. Metastases are uncommon, usually seen in immunocompromised animals. The aim of this paper is to report a case of a transmissible venereal tumor in a female dog spread through the abdomen. The patient had a single mass in the cranial region of the vagina and masses of different sizes adhered to the abdominal wall, mesentery and serosa of organs such as intestine, spleen, urinary vesicle and uterus, visualized on ultrasound examination. Complementary tests such as vaginoscopy and cytomorphological analyzes of the masses in the abdominal cavity and in the vagina were of great importance for the definitive diagnosis. Weekly treatment with 0.5 mg/m2 of Vincristine Sulfate for seven weeks was effective. The importance of this report is the uncommon form of TVT metastasis, as it affected only the serosa of Organs abdominal organs, without compromising their function.